The Novel Atypical Dopamine Uptake Inhibitor (S)-CE-123 Partially Reverses the Effort-Related Effects of the Dopamine Depleting Agent Tetrabenazine and Increases Progressive Ratio Responding - Rotolo, Renee A.; Dragacevic, Vladimir; Kalaba, Predrag; Urban, Ernst; Zehl, Martin; Roller, Alexander; Wackerlig, Judith; Langer, Thierry; Pistis, Marco; De Luca, Maria Antonietta; Caria, Francesca; Schwartz, Rebecca; et al. (Frontiers in Pharmacology, 2019)
Animal studies of effort-based choice behavior are being used to model effort-related motivational dysfunctions in humans. With these procedures, animals are offered a choice between high effort instrumental actions leading to highly valued reinforcers vs. low effort/low reward options. Several previous studies have shown that dopamine (DA) uptake inhibitors, including GBR12909, lisdexamfetamine, methylphenidate, and PRX-14040 can reverse the effort-related effects of the vesicular monoamine transport blocker tetrabenazine, which inhibits DA storage. Because many drugs that block DA transport act as major stimulants that also release DA, and produce a number of undesirable side effects, there is a need to develop and characterize novel atypical DA transport inhibitors. (S)-CE-123 ((S)-5-((benzhydrylsulfinyl) methyl)thiazole) is a recently developed analog of modafinil with the biochemical characteristics of an atypical DA transport blocker. The present paper describes the enantioselective synthesis and initial chemical characterization of (S)-CE-123, as well as behavioral experiments involving effort-based choice and microdialysis studies of extracellular DA. Rats were assessed using the fixed ratio 5/chow feeding choice test. Tetrabenazine (1.0 mg/kg) shifted choice behavior, decreasing lever pressing and increasing chow intake. (S)-CE-123 was co-administered at doses ranging from 6.0-24.0 mg/kg, and the highest dose partially but significantly reversed the effects of tetrabenazine, though this dose had no effect on fixed ratio responding when administered alone. Additional experiments showed that (S)-CE-123 significantly increased lever pressing on a progressive ratio/chow feeding choice task, and that the effective dose (24.0 mg/kg) increased extracellular DA in nucleus accumbens core. In summary, (S)-CE-123 has the behavioral and neurochemical profile of a compound that can block DA transport, reverse the effort-related effects of tetrabenazine, and increase selection of high effort progressive ratio responding. This suggests that (S)-CE-123 or a similar compound could be useful as a treatment for effort-related motivational dysfunction in humans.